Composition of the genus Loricella (Mollusca: Polyplacophora: Loricidae) and the description of two new species - Sirenko, Boris (Zootaxa, 2021)
The genus chiton Loricella is revised. It comprises nine species. Two of these species, L. neoguinensis n. sp. and L. solomonensis n. sp., are described as new. Based on the analysis of morphological features studied using a scanning electron microscope, a revised diagnosis of the genus is provided. The characters diagnostic for this that distinguish it from the related genus Squamophora are as follows: a tubular hollow inside the dorsal scales, bristles on the dorsal side of the girdle, a wide ventral mouth region, a narrow mantle fold covered with simple longitudinally ribbed scales, smooth ventral scales, pits arranged in longitudinal rows in the central area of the tegmentum, and a bicuspid head of the major lateral teeth of the radula.